Principles, operation and customer perception on Islamic charge card in Al-Rajhi Bank Malaysia - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Md Hussain, Muhammad Nasri (IDOSI Publications, 2017)
The introduction of Islamic Credit or Charge Card has given more option on payment transaction. Islamic Cards are based on Syariah compliance instruments and follows the Islamic ways of teaching.This paper will discuss the Islamic Charge Card product offered by Al Rajhi Bank Malaysia and the difference compared to some conventional financial Institution. Islamic Card as a payment that meet at least three criteria of Islamic principle.Card must meet the syariah requirement on lending. It must ditch three essential prohibitions in the Islamic finance which are riba, gharar and maysir.Majority of the customers are satisfied with the Syariah law applied especially with the no minimum payment and no finance charges, Different usage indicators measured in the study show that customers have utilize credit cards for different purposes.